Health literacy and participation in sports club activities among adolescents. Issue 8 (December 2017) - Paakkari, Leena; Kokko, Sami; Villberg, Jari; Paakkari, Olli; Tynjälä, Jorma
Aims: The aim of this research was to compare the levels of perceived health literacy among adolescents who do or do not participate in sports club activities. Organized sport club activities reach a high proportion of adolescents, and have the potential to contribute to the development of their health literacy. Methods: The cross-sectional data on health literacy among school children in Finland (aged 13 and 15, n =3852) were measured, as a part of the Health Behaviour in School-Aged Children (HBSC) study, using the Health Literacy for School-aged Children (HLSAC) instrument. Sports club participation and its association with health literacy were examined in relation to age, gender, family affluence, school achievement, and physical activity. The statistical analyses included cross-tabulation and the multilevel mixed-effects logistic regression analyses. Results: Perceived health literacy was higher among adolescents who participated in sports club activities. This conclusion was valid for boys and girls, for both age groups, among those who were physically active 6–7 days a week, had at least moderate school achievement, and those who belonged to the middle or high affluence families. From the health literacy perspective, participation in sports club activities was especially beneficial for those having low or moderate school achievement level. Conclusions: The sports club setting may work towards equalizing health literacy differences related to school achievement. However, the clubs should ensure that access is available to as many adolescents as possible; by this means they may spread beneficial influences, supporting the development of health literacy among broader population groups.